Ethnographies of schooling in contemporary India - Thapan, Meenakshi (New Delhi Sage, 2014)
The influence of popular culture, media and aggressive marketing of consumer goods all enter the school arena to compete with the more formal aspects of being at school and contribute to the creation of a unique school culture. It is essential to unpack and unravel the rich and engaged world of student culture as it is constructed in school life. Ethnographies of Schooling in Contemporary India attempts to understand meaning and meaning-making in school processes in India as active aspects of a vibrant school culture. We are reminded that students, in any kind of school, are engaged participants in schooling processes. The significance of autobiographical experience in both writing school ethnographies and understanding school life cannot be overemphasised. This volume seeks to also understand this significant aspect of constructing school worlds
Bibliography: p323-30
Keywords: Education--Social aspects; India Education--Aims and objectives--India; India Educational anthropology